Montelukast reduced docetaxel-induced peripheral neuropathy in rats by altering oxidative stress, histopathological damage, and gene expressions - M.D. Karakoç; Ö. Özmen; M.N. Zengin; O. Çiftçi (Brazilian Journal of Medical and Biological Research)
Peripheral neuropathy (PN) is a common side effect of docetaxel (DTX). In this study, we aimed to evaluate the effects of montelukast (MNT), a leukotriene receptor antagonist drug, against DTX-induced PN in rats. Thirty-two male rats were divided into four groups and treated for four weeks: control (sham), DTX (5 mg/kg per week, ip), MNT (10 mg/kg per day, po), and DTX+MNT (5 mg/kg per week, ip + 10 mg/kg per day, po). Behavioral tests (hot plate, tail flick, and rotarod) were conducted. Histopathological, molecular (RT-PCR), and biochemical (ELISA) analyses were performed on sciatic nerve, liver, and serum samples. MNT reduced the malondialdehyde (MDA) levels and increased the superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) parameters in sciatic nerve tissues. Unlike DTX, MNT resulted in increased Bcl-2 gene expression and decreased caspase-3 (Cas-3) and Bax expressions. DTX caused sensory and motor neuropathy, as revealed by the hot plate, tail flick, and rotarod tests. The co-administration of MNT significantly mitigated the sensory and motor neuropathy induced by DTX. MNT improved the levels of NCAM, p38α MAPK, and nuclear factor kappa B (NF-κB), which were impaired in the sciatic nerve tissues due to DTX administration. Additionally, it reduced the levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), which had increased due to DTX. Histopathological examination revealed that DTX-related sciatic nerve damage was mitigated by MNT administration. The results indicated that MNT may have a protective effect against DTX-induced PN in rats.